2005
DOI: 10.1007/s00417-005-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

Posterior capsular opacification affects scanning laser polarimetry examination

Abstract: An artifact introduced by PCO presence can affect SLP measurements reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(8 reference statements)
0
7
0
1
Order By: Relevance
“…In our previous studies we concluded that new RNFL retardation measurements should be obtained after Nd:YAG capsulotomy to serve as a baseline for future comparisons 31,32 . The present research provides more information.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In our previous studies we concluded that new RNFL retardation measurements should be obtained after Nd:YAG capsulotomy to serve as a baseline for future comparisons 31,32 . The present research provides more information.…”
Section: Discussionmentioning
confidence: 58%
“…In our previous studies we concluded that new RNFL retardation measurements should be obtained after Nd:YAG capsulotomy to serve as a baseline for future comparisons. 31,32 The present research provides more information. In fact, a new eye-specific compensation of ASB is also mandatory before obtaining a new baseline of RNFL measurements because PCO removal may cause changes in CPM and CPA.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…2,3 In contrast, we concluded that PCO removal is associated to remarkably significant changes in SLP measurements. Briefly, our results suggest that SLP examination with GDx VCC may overestimate RNFL retardation measurements in PCO-affected eyes.…”
Section: To the Editormentioning
confidence: 58%